2017
DOI: 10.1007/s00436-017-5418-x
|View full text |Cite
|
Sign up to set email alerts
|

Serological dynamics and risk factors of Besnoitia besnoiti infection in breeding bulls from an endemically infected purebred beef herd

Abstract: Bovine besnoitiosis has been deemed a re-emerging disease in Western Europe and considered endemic in Spain, Portugal, France and in some areas of Northern Italy. This report refers to an infection outbreak in a purebred beef herd from Northern Italy involving a large number of bulls. In October 2013, 544 animals were serologically tested with an in-house ELISA followed by a confirmatory Western blot to evaluate Besnoitia besnoiti seroprevalence. A year later, 461 animals were then serologically re-tested toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 33 publications
5
21
1
Order By: Relevance
“…The seroprevalence of besnoitiosis infection in Tibetan sheep was 3.21%, which was in concomitant with the results reported in sheep (4.68%) in Spain (Gutiérrez-Expósito et al, 2017). In current research, area, year and age were found to be associated risk factors of besnoitiosis in Tibetan sheep and yak, which was in accordance with the previous studies (Talafha et al, 2015;Gazzonis et al, 2017). Sex, in the present study was not shown to be a risk factor both in yaks and Tibetan sheep which contradicted with previous results in which had presented male cattle at higher risk of infection (Gazzonis et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The seroprevalence of besnoitiosis infection in Tibetan sheep was 3.21%, which was in concomitant with the results reported in sheep (4.68%) in Spain (Gutiérrez-Expósito et al, 2017). In current research, area, year and age were found to be associated risk factors of besnoitiosis in Tibetan sheep and yak, which was in accordance with the previous studies (Talafha et al, 2015;Gazzonis et al, 2017). Sex, in the present study was not shown to be a risk factor both in yaks and Tibetan sheep which contradicted with previous results in which had presented male cattle at higher risk of infection (Gazzonis et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…In current research, area, year and age were found to be associated risk factors of besnoitiosis in Tibetan sheep and yak, which was in accordance with the previous studies (Talafha et al, 2015;Gazzonis et al, 2017). Sex, in the present study was not shown to be a risk factor both in yaks and Tibetan sheep which contradicted with previous results in which had presented male cattle at higher risk of infection (Gazzonis et al, 2017). However, obvious differences were found in animals of different gender in current study ( Fig.…”
Section: Discussionsupporting
confidence: 71%
“…During the summer period, six of nine bulls got infected. A recent study in an Italian herd also reported high incidences among bulls with twice as much seropositive animals within 1 year (Gazzonis et al., ). In contrast, in our study, serological incidence rates between bulls and females were nearly the same.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, we selected males for these experiments, even though both sexes may be equally infected (Álvarez‐García et al., ). However, bulls are at higher risk of acquiring and transmitting the infection as they serve a large number of cows and they appear to show more acute signs and a higher mortality rate (Álvarez‐García et al., ; Gazzonis et al., ). Moreover, testicles are target organs for B. besnoiti replication and persistence (Kumi‐Diaka, Wilson, Sanusi, Njoku, & Osori, ; Pols, ) and recent studies have provided evidence for the serious consequences of male sterility for herd fertility due to B. besnoiti infection (Esteban‐Gil et al.,; Gazzonis et al., ).…”
Section: Discussionmentioning
confidence: 99%